Development and usability of a website-based depression literacy intervention for university students in Nottingham - Davies, E. Bethan; Morriss, Richard K.; Glazebrook, Cristina (2014)
Purpose: A large proportion of university students experience mental health difficulties, with one review reporting a 30% prevalence rate of depression in this population. Depression affects students’ quality of life and academic performance. Mental health literacy (MHL) encompasses an individual’s knowledge towards, and attitudes and beliefs related to, mental health (e.g. symptom recognition, available treatments/help). Students often do not seek professional help for their mental health, and are more likely to seek support from peers. We have conducted four projects relating to MHL in local students – findings include: a third of students (n=276) screened for elevated depressive and/or anxiety symptomology, with 60% reporting they did not seek professional help; interviews found many students did not perceive GPs as a help source and had concerns about available help; and a vignette-based study found students from non-healthcare/psychology degrees reported lower perceived confidence in helping a friend with depression. Students frequently use internet-based technology; delivering interventions online provides a useful mental health promotion strategy in this population. Based on our findings, we have developed a website-based intervention addressing students’ depression literacy. A usability study with the target population can identify the website’s usefulness and allow us to review it prior to an RCT. Methods: Twenty local undergraduate students will be recruited and will access the website for a week. Afterwards they will complete a usability questionnaire. Results: The usability study will begin in May-June 2014, with an RCT of the website anticipated in late 2014. Conclusion: This study appears to be one of the first website-based interventions to improve depression literacy/MHL in British university students. Feedback from this usability study will be used to alter the intervention prior to an RCT later this year. This RCT will explore the intervention’s effect upon attitudes, intentions and behaviours relating to depression management and help-seeking.